Transformation of Milkfish Bone into Profit: A Financial Study of Milkfish (Chanos chanos) Bone Abon Business in Tanralili District, Maros Regency - Asriadi, Asriadi; Fakhriyyah, Sitti; Hasani, M. Chasyim (PONGGAWA : Journal of Fisheries Socio-Economic, 2024)
This study aims to determine the profitability of milkfish bone floss business (Chanos chanos) in Tanralili District, Maros Regency and analyze the feasibility of milkfish bone floss business in Tanralili District, Maros Regency. The research was conducted in March - April 2022 in Maros Regency. Sampling in this study used the census method, which is a sampling technique where all members of the population are used as samples. The data sources used are primary data and secondary data and then analyzed using income analysis and business feasibility analysis (short term). From the results of the study it was found that the profit from the milkfish bone shredded business in Tanralili District, Maros Regency amounted to Rp. 30,860,083,- / year and financially the milkfish bone shredded business at Cahaya Bandeng UMKM in Tanralili District, Maros Regency is said to be feasible to continue after a feasibility analysis.